PENGARUH KOMPETENSI, INDEPENDENSI, TEKANAN WAKTU, DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT - Winda Kurnia; Khomsiyah Khomsiyah; Sofie Sofie (Jurnal Akuntansi Trisakti, 2014)
The purpose of this study is to analyze the effect of competence, independence, time pressure, and ethics of auditors on the quality of audit. This research is expected to improve the quality of audit conducted by an auditor who has the competence and independence. The population used in this research are auditors who work in the public accountant office in jakarta of which is there are as many as 171 of respondents. This study used multiple regression analysis. The results of this study are (1) The competence has significant effect on the quality of audit, (2) The independence has significant effect on the quality of audit, (3) The time pressure has significant effect on the quality of audit, and (4) The ethics has significant effect on the quality of audit. The implication of this research for institution that is public accountant office as an evaluation on upon the performance of auditors to increase the competence, independence, time pressure, and ethics of auditors to produce a good quality of audit in terms of the disclosure of the financial statements and can help investors and other parties concerned to avoid the possibility of fraud by those who use the audit results.